A role-model for data policies? Qualitative study on the governance of health data in Denmark. Issue 4 (December 2022) - Martani, Andrea; Egli, Sophia Mira; Geneviève, Lester Darryl; Elger, Bernice Simone; Wangmo, Tenzin
Highlights: Denmark has renowned system of data governance for the reuse of health data. Limitations related to data access for industry and foreign institutions exists. The features of the Danish data landscape are embedded in its culture and history. Emulating Danish health data policies elsewhere might be difficult. Abstract: Objectives: Denmark has invested a lot in the branding of its health data landscape as a role model. We explored to which extent this holds true, with a focus on data access for secondary uses and research, to also see what other countries can learn from the Danish experience. Methods: Semi-structured interviews were conducted with 15 Danish stakeholders working as policy makers, researchers or in public administration and having experience with the health data landscape. The transcripts underwent Qualitative Analysis following the QUAGOL framework. Results: The analysis focused on three themes:(i) the Danish health data landscape is considered very effective, but also features limitations regarding the secondary use of data, especially for collaborations with industry and international stakeholders;(ii) the development of institutional structures and the attitude of the Danish population towards data are intertwined with historical and cultural factors, limiting the possibility to emulate the Danish data landscape elsewhere; and(iii) technological advancements might hold challenges for the future sustainability of the Danish data landscape. Conclusions: The Danish model, although often branded as ideal, also relies on a balance between extensive data usage and persisting limitations. Hence, it should not be considered a 'dream' system to blindly emulate, but a valuable example of how such balance can be found, without forgetting that the latter requires continuous adaptation. Since the willingness of a population to approve of data usage may change due to privacy concerns, regular political renegotiations of the ethical underpinning of any health data landscape are crucial for their sustainability.